GAYA BAHASA BERDASARKAN LANGSUNG TIDAKNYA MAKNA DALAM PANTUN ADAT JAMBI: KAJIAN STILISTIKA - Priyanto Priyanto (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2016)
ABSTRACT The purpose of this study is to describe the style of language based on the directness of the meaning contained in the traditional pantun Jambi. The method used in this research is descriptive qualitative method, with stilistika approach. The data in this study is the style of figurative language which is the scope of stylistic analysis. The data source in the research is the rhyme contained in the book